A Desktop Review of Linguistic Practices in Higher Education Post #FeesMustFall Protests: An Appraisal of Academy and Multilingual Citizenship - Soyiso Khetoa (E-Journal of Humanities, Arts and Social Sciences)
Student protests nationwide in the form of #FeesMustFall in South Africa between 2015 and 2016 catalyzed a national conversation on decolonization, inclusivity and linguistic transformation in higher education. This qualitative desktop review examines the evolution of linguistic practices in a South African university post-protests, focusing on the intersection of academic discourse and multilingual citizenship. This review is premised on Language Management Theory which endorses deliberate processes which seek to influence language behaviour among language users. Through an analysis of secondary sources, the study explores the implications of linguistic practices for epistemic justice, academy, and multilingual citizenship post #FeesMustFall demonstrations. The findings highlight the continued hegemony of English in communication, classroom interactions, and research. However, the university has taken steps to promote multilingualism by offering African language courses to first-year students in humanities and engineering programs. The institution also recognizes linguistic diversity as a valuable asset that empowers people in multicultural and multilingual settings. This review contributes to the ongoing discourse on language, power, and knowledge production in African higher education, providing insights for policymakers, educators, and language practitioners who are committed to creating inclusive and equitable academic spaces.